Разработка составов теплоизоляционного материала на основе красного шлама - Кушнерова, Лилия (Optimum, 2015)
The results of research of porous thermal insulating materials production on the base of industrial waste are presented in the article. The influence of red mud and microsilica on the properties of heatinsulation are considered
Keywords: теплоизоляция; пористый; газообразование; отходы промышленности; 691.33